Views of Al-Anbar Nurses towards Nutrition Nurses - Alhiti, Hazim (Algerian Journal of Biosciences, 2023)
This study illustrated the healthcare nurses' opinions towards the importance of nutrition nurses. It is a prospective study that included 101 Al-Anbar nurses, all of whom had five years or above of healthcare experience in different health institutions of the Al-Anbar health directorate. The authors distributed an online survey from 4th -12th February 2022. There were 101 healthcare staff aged (27-55) years. There were 36 females (35.6 %), and 65 (64.4 %) males. Eighty-five of them (84.1 %) recommended a nutritional faculty in the Iraqi Ministry of Health. A nutrition nurse is an essential vacation in any hospital